Pemenuhan Gizi Ikan melalui Diversifikasi Olahan Hasil Perikanan dan Sayur Lokal Kalimantan Tengah - Tyas Wara Sulistyaningrum; Ivone Christiana (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
The aim of this research is (1) to develop diversification of fish as food into healthy processed foods with nutrition, and (2) to create processed fish products as an alternative local food. This research was carried out from August to September 2021. The implementation and testing of the organoleptic properties of the samples was carried out at the Fishery Product Processing Technology Laboratory, Department of Fisheries, Faculty of Agriculture, University of Palangka Raya and chemical testing was carried out at the Palangka Raya Goods Quality Testing and Certification Center. The result of this research (1) diversification of processed local food from snakehead fish (Channa striata) and kalakai (Stenochlaena palustris) has resulted in processed kalakai snakehead fish nuggets that are preferred, which completed the nutritional value and meet the quality requirements. (2) Kalakai snakehead fish nuggets could be used as an alternative to local food with local raw materials that are easily available and could fulfill the nutrition during the Covid-19 pandemic. Keywords: Diversification, processed fish product, local vegetables, local foods